HUBUNGAN POLA MAKAN FAST FOOD DAN AKTIVITAS FISIK DENGAN KEJADIAN OBESITAS PADA ANAK USIA 9-11 TAHUN DI MI SA’ADATUL MAHABBAH PONDOK CABE - Herliana Fajrini; Ayatun Fil Ilmi; Lela Kania Rahsa (Syntax Corporation Indonesia, 2022)
Obesity is a person who has excess body weight associated with excessive accumulation of body fat. Obesity is influenced by many things, one of which is diet and physical activity. This study aims to determine the relationship between diet and physical activity with the incidence of obesity in children aged 9-11 years at MI Sa'adatul Mahabbah Pondok Cabe. This is a quantitative research that uses a correlation analytic research design with a cross sectional approach with the aim of knowing the relationship between the independent variable and the dependent variable. The data were collected using a questionnaire, the sampling technique was using simple random sampling with certain inclusions and exclusions and the sample size was 182 students calculated by the Lameshow formula. From the univariate results for children aged 9- 11 years at MI Sa'adatul Mahabbah, it was found that 58 people (60.4%) often did fast food, then 55 people (57.3) did physical activity. %) and 36 children (37.5%). The results of the bivariate study showed that most of the students were obese by frequently eating fast food, namely 19 people (32.8%) with a significant chi-square test result or (p-value = 0.028) and most of the students had obesity in the category of sometimes sometimes doing physical activity, namely 27 people (49.1%) with the results of the chi-square test with (p-value = 0.018). So it can be concluded that there is a relationship between diet and physical activity with obesity in children aged 9-11 years at MI Sa'adatul Mahabbah. Suggestions that can be given in this study for students are expected to prioritize and improve the quality of nutrition and body health in maintaining a healthy diet and physical activity so that students are expected to feel comfortable living a healthy lifestyle. Increased information about the risk of obesity and the role of teachers in schools, health workers and family support is very necessary.